Capacity for complexity, intelligence and personality. - Comaroff, Yael (My University, 2012)
The chaos and instability which dominates the organisational environment of today often leads to complexity – continuous ambiguity and change. Leaders and managers are required to be able to make effective decisions in these highly abstract circumstances hence selecting and managing employees who have the capacity to handle complexity has become of great importance (Yuksel, 2011). The Career Path Appreciation (CPA), which is an interview-based technique assessing complexity, has become popular in the South African context however it is extremely costly and organisations need to be assured that the financial expense results in a valid, reliable and unique assessment. Therefore, this research explored the associations between three different assessment measures: the (CPA), the Wechsler Adult Intelligence Scale III (WAIS-III) and the California Psychological Inventory (CPI). The aim of the study was to investigate whether personality and/or intelligence were associated with one’s capacity for complexity in any way and whether the CPA was distinct in any way from other personality and/or intelligence measures. The research was based on archival data collected from a final sample of 266 managers from a large international manufacturing organisation situated in South Africa. The only biographical information attained was for age of the individuals. Correlation results found that only one of the subscales of the WAIS-III, Similarities, was significantly and moderately correlated with current capacity for complexity. In terms of future potential, only Similarities and Block Design were found to have significant positive correlations. Many more of the personality factors were found to be related to capacity for complexity. Current capacity for complexity was moderately correlated with Achievement via Independence, Independence, Empathy, Social Presence, Capacity for Status and Flexibility. For future capacity for complexity, significant moderate relationships were found with Flexibility, Social Presence, Achievement via Independence, Intellectual Efficiency, Sociability and Empathy. Chi-Squared Tests of Association were conducted to assess the nominal data of CPA Style, which found that of all the WAIS-III subscales and overall scales, only Digit Symbol Coding, Similarities and Block Design showed evidence of significant relationships. Five CPI factors proved to be significantly associated with CPA Style: Empathy, Tolerance, Achievement via Independence, Intellectual Efficiency and Psychological Mindedness. A series of multiple regressions were conducted in order to find out which personality and intelligence facets predicted current and future capacity for complexity. It was found that forty-one percent of the variance in current capability was explained by age, Dominance, Sociability, Independence, Good Impression, Wellbeing, Achievement via Independence, Similarities and Block Design. In terms of future capability forty-eight percent of the variance in Mode was explained by age, Dominance, Social Acceptance, Good Impression, Achievement via Independence, Flexibility, Similarities, Block Design and Comprehension. The research concluded that the CPA assessment is a highly effective and unique technique for outlining an individual’s capacity for complexity even though it is an extremely costly assessment tool in South Africa. Although aspects of the WAIS-III and the CPI were found to be related to capacity for handling complexity, these results were not strong enough to conclude that the WAIS-III and the CPI overlap with the constructs measured in the CPA or could be used in its place.
Keywords: Complexity; Intelligence; Personality